Genetic Diversity and Demographic History of the Shaggy Soft-Haired Mouse Abrothrix hirta (Cricetidae; Abrotrichini) - Valdez, Lourdes; D’Elía, Guillermo (Frontiers in Genetics, 2021)
Genetic information on species can inform decision making regarding conservation of biodiversity since the response of organisms to changing environments depend, in part, on their genetic makeup. Territories of central-southern Chile and Argentina have undergone a varying degree of impact during the Quaternary, where the response of local fauna and flora was rather species-specific. Here, we focus on the sigmodontine rodent Abrothrix hirta, distributed from 35° S in Chile and Argentina to northern Tierra del Fuego. Based on 119,226 transcriptome-derived SNP loci from 46 individuals of A. hirta, we described the geographic distribution of the genetic diversity of this species using a maximum likelihood tree, principal component and admixture analyses. We also addressed the demographic history of the main intraspecific lineages of A. hirta using GADMA. We found that A. hirta exhibited four allopatric intraspecific lineages. Three main genetic groups were identified by a Principal Component Analysis and by Ancestry analysis. The demographic history of A. hirta was characterized by recent population stability for populations at the northernmost part of the range, while southern populations experienced a recent population expansion.